A model of unfrozen water content and its transport in icy permafrost soils: Effects on ground ice content and permafrost stability. (24th October 2019) - Fisher, David A.; Lacelle, Denis; Pollard, Wayne
Abstract: Knowledge of the amount of unfrozen water and its migration in permafrost soils is important for understanding physico‐chemical and biological processes. Here, we developed sub‐routines in FREZCHEM and embedded them in the WATEREGO2 soil environmental model to: (a) estimate unfrozen water content under changing soil temperatures and water–ice phase changes; and (b) determine the effects of Van der Waals (VdW) and rheological forces driven by seasonal temperature variations on the transport of residual water and the long‐term evolution of ground ice content over depths of 30 m. Together, the seasonal thermal regime and associated VdW and rheological forces on the transport of residual water lead to the evolution of distinct zones of ice‐enrichment: near the surface of permafrost, at 3–5 m, 11–13 m and 17–19 m depth. The depths of ice enrichment are a function of soil thermal diffusivity, and the time needed to evolve the ground ice content is dependent on soil type, soil water chemistry and permafrost temperature. The model can explain observed variations with depth in ground ice content of icy permafrost soils and indicate that these conditions evolve over time. The findings can be used to assess the stability of permafrost to climate change under different temperature scenarios.